Changing employee behavior : a practical guide for managers - Nik Kinley, Director and Head of Talent Strategy, YSC Ltd, UK, Shlomo Ben-Hur, Professor of Leadership & Organizational Behavior, IMD, Switzerland (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2018)
240 p.